Research progress of hypoxia inducible factor 1α in the mechanism of diabetic kidney disease - ZHANG Yahui, BAI Qiong (Jichu yixue yu linchuang, 2024)
Hypoxia-inducible factor-1α (HIF-1α) is a nuclear transcription factor. Under high glucose and hypoxia conditions, the expression of HIF-1α is elevated, result in the increased expression of its downstream target genes VEGF, HO-1 and BNIP3, which affect angiogenesis, extra cellular matrix deposition, iron metabolism, and mitophagy, participating in the occurrence and development of diabetic kidney disease (DKD). In addition, HIF-1α promotes inflammation and renal fibrosis by affecting the production of cytokines in DKD.